Durable, absorbent spunlaced fabric structures - SUMMERS, JAMES THOMAS; CRUISE, CHARLES CLAYTON; PETERSON, ROBERT HOWE (2002)
This invention relates to making nonwoven fabrics which are durable for machine washing and durable for other wet and hard use or abusive applications. The inventive fabrics comprise two layers of fabric sheet bonded together at closely spaced locations where the bonding includes fibers from both fabrics thoroughly involved with the binder. The inventive fabrics retain the qualities of a spunlaced nonwoven fabric which include low cost, comfort, drapability, softness, absorbency, breathability and others while having the durability comparable to traditional knitted or woven fabrics.